Descriptions of two new species of earthworm of the genus Pheretima Kinberg, 1867 (Oligochaeta: Megascolecidae) from Mekong delta - Vietnam - Tung, Nguyen Thanh (Academia Journal of Biology, 2012)
In this article describes two new species of earthworm (Pheretima mangophila Nguyen, sp. n. and Pheretima thaii Nguyen, sp. n.) are found in Mekong delta - Vietnam. Pheretima mangophila Nguyen, sp. n. (figure 2): First dorsal pore in 12/13. Spermathecal pores two pairs in 5/6/7. Genital papillae absent. Septa 5/6 - 7/8 thickish, 8/9 and 9/10 absent, 10/11 - 12/13 thin. Intestinal caeca, manicate. Integumentary micronephridia in front of clitellum drop of water- shaped. Pheretima thaii Nguyen, sp. n. (figure 3): First dorsal pore in 12/13. Spermathecal pores three pairs in 5/6/7/8. Genital papillae absent. Septa 5/6/7thickish, 8/9 and 9/10 absent, 7/8 and 10/11/12 thin. Intestinal caeca, manicate.